2017
DOI: 10.17776/cumuscij.297820
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Various Laser Surface Modifications on SBS of Titanium and Zirconium Oxide Substructures

Abstract: In prosthodontics, to increase the bonding of metals with porcelain by several means including laser surface treatments is still an important research topic. The current study was undertaken to evaluate the influence of surface treatment with Ho:YAG, Er:YAG, and Nd:YAG lasers on the shear bond strength (SBS) of low fusion dental porcelain to titanium and zirconium oxide substructures. Titanium (n=70) and zirconium oxide (n=70) specimens were categorized into 7 study groups (n=10): sandblasting, Er:YAG 1.5W and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Additionally, this discrepancy could be attributed to a difference in the type of laser: we used a nanosecond fiber laser, whereas the cited study used an Nd:YAG laser. In their study, Saygın et al [39] revealed that an Nd:YAG laser produced better results, an Er:YAG laser produced similar results, and a Ho:YAG laser produced lower results compared to sandblasting. As it can be clearly inferred, the type of laser affects the bond strength.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this discrepancy could be attributed to a difference in the type of laser: we used a nanosecond fiber laser, whereas the cited study used an Nd:YAG laser. In their study, Saygın et al [39] revealed that an Nd:YAG laser produced better results, an Er:YAG laser produced similar results, and a Ho:YAG laser produced lower results compared to sandblasting. As it can be clearly inferred, the type of laser affects the bond strength.…”
Section: Discussionmentioning
confidence: 99%
“…Many works have also been done on the titanium surface treatment, to obtain an accurate bonding strength of the metal-low-fusing porcelain system. Some of them concern thermal treatment, oxidation [ 16 , 17 , 18 ], modification by chemical etching [ 19 , 20 , 21 , 22 , 23 ], and laser treatment [ 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%